ANALISIS PENGARUH KUALITAS PRODUK, CITRA MEREK, PERSEPSI HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen teh dalam kemasan merek Teh Botol Sosro di Kota Semarang) - Firdausi, Alfa Nurrahman; Khasanah, Imroatul (Faculty of Economics and Business Diponegoro University, 2017)
The business competition of packaged tea products is increasing, as indicated by the growing number of new brands of bottled tea in packaging. Conditions must be understood by bottled tea manufacturers by improving marketing strategies through improving product quality, brand image, appropriate pricing strategies and increasingly attractive promotions for consumers interested in deciding to purchase their products. The purpose of this research is to examine the effect of product quality, brand image, price perception and promotion on purchasing decision of Sosro Bottle Tea product.The population in this study were consumers who bought Sosro bottle tea in Semarang City, while the sample was as many as 100 respondents who got by using accidental sampling sampling technique, that is the researcher chose respondents by way of respondents in crowded places seller Sosro tea seller in City. The type of data used is primary data, using the method of collecting data kusioner.The result of analysis by using multiple regression is product quality have positive effect to purchasing decision. Brand image positively affects purchasing decisions. Price perceptions have a positive effect on purchasing decisions. Promotion positively affects purchasing decisions.